Analisis Kemampuan Berpikir Kritis Dan Science Motivation Siswa Pada Pembelajaran Pesawat Sederhana - Indah Sukmawati; Joko Siswanto; Fenny Roshayanti (Jurnal Penelitian Pembelajaran Fisika, 2020)
This study aims to determine the level of critical thinking skills and science motivation of students in learning science. The population in this study all students of class VIII SMP N 3 Pemalang were 10 classes with 317 students. The research sample was randomly selected with a sample of one class of 31 students. The study was conducted on January 4, 2020, data collection techniques in the form of tests and questionnaires. The test is used to determine students' critical thinking skills in learning science in simple plane materials. While the questionnaire is used to determine the level of science motivation of students in learning Natural Sciences. Descriptive quantitative data analysis and percentage. The results showed the level of critical thinking skills of Pemalang N 3 Middle School students was 35.48% from the high and medium category. While the level of science motivation of Pemalang N 3 Middle School students was 35.50% from the high and medium category. This shows that the ability to think critically and the level of science motivation of students is still quite low. So we need a learning model that can improve students' motivation and critical thinking skills.